2018
DOI: 10.1155/2018/2737982
|View full text |Cite
|
Sign up to set email alerts
|

Talus Bipartitus: A Rare Anatomical Variant Presenting as an Entrapment Neuropathy of the Tibial Nerve within the Tarsal Tunnel

Abstract: Tarsal tunnel syndrome is an entrapment neuropathy of the tibial nerve within the tarsal tunnel that lies beneath the retinaculum on the medial side of the ankle. It is often underdiagnosed. Talus bipartitus is a rare anatomical variant; only a few cases have been described in medical literature. We report a case of a 36-year-old female with tarsal tunnel syndrome secondary to a talus bipartitus undergoing surgical treatment with good clinical outcome. To our knowledge, talus bipartitus presenting as tarsal tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…After a review of the literature, few cases have previously described a skeletal abnormality as a cause of TTS. 2,3,4,5,6,16 Although one such case has described a similar bipartite talus as a cause of TTS, this case highlights how a relatively common entity in an os trigonum may seem similar to a bipartite talus and adds to the literature surrounding this rare entity, its pathological consequences, and prognosis after its removal. 6…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…After a review of the literature, few cases have previously described a skeletal abnormality as a cause of TTS. 2,3,4,5,6,16 Although one such case has described a similar bipartite talus as a cause of TTS, this case highlights how a relatively common entity in an os trigonum may seem similar to a bipartite talus and adds to the literature surrounding this rare entity, its pathological consequences, and prognosis after its removal. 6…”
Section: Discussionmentioning
confidence: 73%
“…[10][11][12] However, in smaller fragments, surgical removal without additional fixation has also been shown to have satisfactory outcomes. 6,10,12 In this case, the patient did not require additional subtalar fixation because of the small articulation with the posterior facet and subtalar stability after removal. In addition, due to its location and role in the patients TTS, fixation of the posterior talar fragment could not be pursued.…”
Section: Discussionmentioning
confidence: 88%
“…ASM is a condition that manifests itself with the increase in clinical problems caused by advanced age (13)(14)(15)(16)(17). ASM, whose incidence was reported as 0.7%-5.5% in cadaver studies, is usually unilateral and it has been reported to be more (4,18,19). Reported that the presence of ASM causes nerve compression at a rate of 7-8% in tibial nerve compressions (13).…”
Section: Discussionmentioning
confidence: 99%
“…1,5 The accessory muscles were observed by several authors in approximately 7e8% of body dissection, rarely presented as a cause of tibial nerve compression either extrinsic or intrinsic. 2,5 Conservative management should be tried first as some cases may respond well to conservative treatment. 9 Other patients may respond to botulinum toxin A injection.…”
Section: Discussionmentioning
confidence: 99%